Postharvest Biological Control of Guatemalan Potato Moth, Tecia solanivora, by Trichogramma euproctidis and Blattisocius tarsalis - Jorge Gavara; Mihaela Paris; Estrella Hernández-Suárez; Tomás Cabello; Juan Ramón Gallego; Ana Piedra-Buena (Agronomy, 2023)
Tecia solanivora (Povolný 1973), is a quarantine pest in Europe. Identified in Guatemala in the 1970s, it spread throughout Central and South America, reaching the Canary Islands in 1999 and mainland Spain in 2015. The pest has caused prohibitive economic losses both in the field and in storage, where losses can reach 100%. In the absence of approved chemical treatments, the use of an egg predatory mite, Blattisocius tarsalis (Berlese 1918), and the egg parasitoid, Trichogramma euproctidis (Girault 1911), is being studied for use in storage. Previous laboratory studies have confirmed their potential for use in non-refrigerated stores, typically between 15 and 20 °C. In the present work, we compared the efficacy of both natural enemies under semi-storage conditions. We observed that while both T. euproctidis and B. tarsalis reduced the T. solanivora populations (with an efficacy of 82.95 ± 7.32% and 49.06 ± 2.69%, respectively) and the number of mites per tuber, only B. tarsalis resulted in undamaged tubers (65%). For this reason, the mite was selected and tested in storage conditions, obtaining promising results in the protection of infested tubers, suggesting potential for further investigation, adaptation and standardization of its use in real conditions.